The menstrual cycle and football: The experiences of African women football players - Mkumbuzi, N. S.; Dlamini, S. B.; Chibhabha, F.; Govere, F. M.; Manda-Taylor, L. (Science and Medicine in Football, 2022)
Background: The menstrual cycle is a normal biological process in women and girls. However, it is often the reason why they tend to be excluded from football medicine research. Consequently, our understanding of the menstrual cycle and football performance is still limited, especially in African women football players. Aim: The study aimed to explore African women football players` current and historical menstrual cycle status, menstrual symptoms, lived experiences, and perceptions of the menstrual cycle. Methods: Women football players at the COSAFA Women's Championship 2020completed demographic questionnaires and the Moos Menstrual Distress Questionnaire. Results: The main findings were that 90% of the players did not use contraceptives, . Most of the players had access to their preferred choice of sanitary product; however, 36% used alternatives such as old rags during their periods, . The most commonly reported symptoms during menses were abdominal cramps (53%), headache (41%), mood swings (41%) and irritability (47%). Further, players reported irritability (48%), mood swings (52%), and breast tenderness (48%) in the week before their period. Conclusion: The low use of contraceptives is likely due to community level socio-cultural factors. While the use of old rags as impromptu sanitary products is likely because they cannot always afford their preferred choice. Menstrual symptoms can affect training and competition; therefore, team support personnel should be aware of the menstrual cycle`s implications for African women football players and their effect on athletic performance and well-being. Additionally, team support personnel ought to be mindful of African women football players` socio-economic and religio-cultural contexts and their interaction with biological processes such as the menstrual cycle and contraceptive use.